Gender Norms and Domestic Abuse: Evidence From Australia - Yinjunjie Zhang; Robert Breunig (Institute of Labor Economics (IZA), 2021)
Australia conforms to the gender norm that women should earn less than their male partners. We investigate the impact of violating this cultural norm on the incidence of domestic violence and emotional abuse against women and men in Australia. Violating the male breadwinning norm results in a 35 per cent increase in the likelihood of partner violence and a 20 per cent increase in emotional abuse against women. We find no effect on abuse against men. The strong effect of violating the gender norm on abuse against women is present across age ranges, income groups and cultural and educational backgrounds.
Keywords: J12; K42; D31; 330; domestic violence; gender identity norm; relative income